2019
DOI: 10.1111/jfbc.13001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of barley and/or dates attenuate hypercholesterolemic‐induced endometrial dysfunction in Wistar albino rats via alleviation of apoptotic pathways and enhancing oxidative capacity

Abstract: Our study was conducted to characterize the efficacy of barley and/or date palm fruits (10%) in alleviation of hypercholesterolemic endometrial insults in obese rat model. Sixty‐four Wistar albino rats were randomized into eight groups (n = 8); control, hypercholesterolemic‐ and hypercholesterolemic‐treated groups. Animals were subjected to treatment for 4 months. After sacrifice, serum and uterine tissues were collected and processed for biochemical, histological, immunohistochemical, and electron microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However, the study of Karimi Jashni et al ( 2016 ) showed that the consumption of P. dactylifera extract due to the presence of estrogen‐like compounds reduced the LH to FSH ratio and the number of cystic follicles, modulated estrogen and androgen synthesis, and increased the number of secondary and antral follicles (Karimi Jashni et al., 2016 ). The estrogenic compounds of this plant extract can be used to treat uterine disorders as they have been shown to reduce endometrial tissue degeneration, necrotic patches, and hyperplasia in endometrial glands (El‐Mansi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study of Karimi Jashni et al ( 2016 ) showed that the consumption of P. dactylifera extract due to the presence of estrogen‐like compounds reduced the LH to FSH ratio and the number of cystic follicles, modulated estrogen and androgen synthesis, and increased the number of secondary and antral follicles (Karimi Jashni et al., 2016 ). The estrogenic compounds of this plant extract can be used to treat uterine disorders as they have been shown to reduce endometrial tissue degeneration, necrotic patches, and hyperplasia in endometrial glands (El‐Mansi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The estrogenic compounds of this plant extract can be used to treat uterine disorders as they have been shown to reduce endometrial tissue degeneration, necrotic patches, and hyperplasia in endometrial glands (El-Mansi et al, 2019). (Kumar et al, 2019).…”
Section: Phoenix Dactylifera (Date Palm)mentioning
confidence: 99%
“…Previous studies have demonstrated that hypercholesterolemic rats showed a significant reduction in the antioxidant activities of CAT, and SOD, in addition to an increased number of atretic follicles and relatively decreased antral follicles (Cordier, et al, 2013) [14]. In the same vein, a study by Lin, et al (2017) [15] reported a decreased number of small follicular populations in the ovaries of hypercholesterolemic dams (El-Mansi, et al, 2019) [16].…”
Section: Introductionmentioning
confidence: 95%
“…In C57BL/6 mice fed with a high-fat diet, proliferating cell nuclear antigen (PCNA) expression decreased, and activated B cells (NF-κB) and the nuclear factor κ-light chain enhancer of the peroxisome proliferator-activated receptor gamma (PPAR gamma) signaling pathway increased ( Cheng et al, 2018 ). With the increase in OS, the high-fat diet led to increased endometrial cell apoptosis by increasing the expression of 8-hydroxydeoxyguanosine (8-OHdG) ( Heard et al, 2016 ); compared with the control group, the high-fat diet in the hypercholesterolemia rat model promoted oxidative and inflammatory stress and significantly increased tumor necrosis factor-α (TNF-α) and F4/80 macrophage infiltration ( El-Mansi et al, 2019 ). The aforementioned studies all suggest that the impaired lipid pattern in PCOS patients with MetS can activate ROS through a variety of molecular adjustment mechanisms, resulting in an imbalance in OS in the body, especially in the endometrial region, which in turn affects ER and leads to adverse pregnancy outcomes.…”
Section: Metabolic Disorders and Oxidative Stressmentioning
confidence: 99%